2016
DOI: 10.3991/ijet.v11i02.5053
|View full text |Cite
|
Sign up to set email alerts
|

IPad in Elementary School Math Learning Setting

Abstract: Abstract-The aim of this study was to investigate the difference between the effect of using traditional teaching instruction and using iPad to teach math for first grade students. This study was conducted in one private elementary school in Jordan. The study used a quasi-experimental control design. Students have access to a few math software and websites that was downloaded to improve their math skills. Every student in the experimental group will have a personal iPad to be used during their math class perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
4
10
0
2
Order By: Relevance
“…Apart from software, the iPad has been used as a medium for learning mathematics [39]. This research was conducted in a 1st-grade elementary school in Jordan.…”
Section: 2mentioning
confidence: 99%
“…Apart from software, the iPad has been used as a medium for learning mathematics [39]. This research was conducted in a 1st-grade elementary school in Jordan.…”
Section: 2mentioning
confidence: 99%
“…Another study investigated the difference between the effect of using traditional teaching instruction and using a tablet to teach mathematics for students of first grade of an elementary school in Jordan. The study demonstrated that the use of tablets for studying mathematics was encouraging for teachers and students as part of the learning process; it also showed that in some specific cases students improved their mathematics skills [5].…”
Section: Introductionmentioning
confidence: 87%
“…Many school children are proficient with technology [11][12][13][14] that can facilitate their learning. Often, however, a lack of technology-related pedagogy skills amongst teachers can be an issue [15].…”
Section: Introductionmentioning
confidence: 99%